Microencapsulated cell tracking. (7th December 2012) - Arifin, Dian R.; Kedziorek, Dorota A.; Fu, Yingli; Chan, Kannie W. Y.; McMahon, Michael T.; Weiss, Clifford R.; Kraitchman, Dara L.; Bulte, Jeff W. M.; Mulder, Willem J. M.; McMahon, Michael T.; Nicolay, Klaas
<x xml:space="preserve">Abstract</x> Microencapsulation of therapeutic cells has been widely pursued to achieve cellular immunoprotection following transplantation. Initial clinical studies have shown the potential of microencapsulation using semi‐permeable alginate layers, but much needs to be learned about the optimal delivery route, in vivo pattern of engraftment, and microcapsule stability over time. In parallel with noninvasive imaging techniques for 'naked' (i.e. unencapsulated) cell tracking, microcapsules have now been endowed with contrast agents that can be visualized by 1H MRI, 19F MRI, X‐ray/computed tomography and ultrasound imaging. By placing the contrast agent formulation in the extracellular space of the hydrogel, large amounts of contrast agents can be incorporated with negligible toxicity. This has led to a new generation of imaging biomaterials that can render cells visible with multiple imaging modalities. Copyright © 2012 John Wiley & Sons, Ltd.